A Comprehensive Review of Professional Attitude: An Analysis of Scopus-Enrolled Journals from 2003 to 2022 - Allah Bachayo Rajar, Abdul Manan Soomro, Amjad Azam, Washin Das, Partab Puri, Zameer Hussain Baladi, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The research aims to investigate and assess the existing knowledge surrounding professional attitudes within this journal selection for 20 years. The study explores the year-wise distribution of published manuscripts, examines the various formats utilized in these publications, and investigates the patterns of languages used in the manuscripts. Through this analysis, the research aims to provide a comprehensive overview of the literature on professional attitude and identify potential gaps or trends in research. Methods: The data of manuscripts relating to "Professional attitudes" on the three modules, year-wise distribution, document format/type, and manuscript language were examined on the Comma-Separated-Value (CSV) file from the Scopus-Database. The data helped meet the study objectives. The data was examined, tabulated, and sorted results in the Al-Nafees Central Library of Ibn-e-Sina University Mirpurkhas Sindh Pakistan in June 2023. Results: Total 1907 manuscripts published with the average of 95.3% on Twelve Formats/Types; 1558, 81.7 articles, 153, 8% review papers, 9, 0.4% books, 75, 4% book-chapters, 69, 3.6% conference papers, 4, 0.2% conference reviews, 1, 0.05% data-paper, 5, 0.26% editorials, and errata, 9, 0.47% letters, and notes, and 10, 0.52% short surveys. The 1688, 88.5% manuscripts were published in English language as supporting global language out of 29 languages. Practical Implication: The evaluation and assessment of papers or presentations presented to a conference by academics, scholars, or specialists in a specific topic is referred to as a conference review. Review articles synthesize and analyze the existing literature on a particular topic. These articles will likely provide an exhaustive summary of the research conducted on professional attitude Conclusion; Based on the findings of manuscripts relating to "Professional attitudes" published in a variety of formats/types and languages, the majority were published as articles, which were the most common format for disseminating knowledge on professional attitudes, followed by review papers, book chapters, conference papers, and other eight formats. A large proportion of research was published in English, indicating that it is widely used as a global language for scholarly communication. Keywords: Professional attitude, attitude, ongoing learning, Ibn-e-Sina University, communication skills, and body language.